Обучение префразированию на занятиях ESL - Лутай, Наталия Викторовна; Бесараб, Татьяна Петровна (Національний університет "Острозька академія", 2020)
В статье рассматриваются способы развития навыков перефразирования на занятиях. Обозначены такие факторы, ограничивающие возможности студентов, как недостаточные фоновые знания и словарный запас, которые также могут играть роль в процессе обучения. Эффективное написание резюме текста требует навыков критического мышления. Суть заданий в основном заключается в построении общей концептуальной cструктуры на основе анализа отрывка и синтеза информация полученной из него. Исследовательское обучение (IBL) используется в качестве стратегии, которая поощряет независимое мышление при написании резюме в аудитории. Особое внимание в статье уделено необходимости развития навыков говорения.

The article enlightens some ways of developing paraphrasing skills in the ELS classroom. The factors limiting students’ abilities, such as insuffient background knowledge and vocabulary, which can also affct the process of learning, are indicated. Effctive summary writing requires critical thinking skills. So, the goal of tasks is mainly focused on constructing a common conceptual framework based on the analysis of passages and synthesis of information obtained from them. Inquiry based-learning (IBL) can be applied as a strategy that encourages independent thinking when writing resumes in the classroom. To master paraphrase skills, special attention should be paid to vocabulary, e.g. morphology as well as grammar and syntax since students face defiite diffilties with writing tests. One of possible ways of solving this problem is to teach students to recognize and use link words and word-markers, as well as to know how phrase and subordinate sentences function. What’s more, it is essential for teachers to emphasize the rules of word formation and ways of interpreting idioms. Particular attention is paid to the necessity of developing speaking skills. In this article some exercises that illustrate the problems of paraphrasing are given to show how students can manipulate a text to paraphrase short passages from it.
Teaching paraphrasing in second language classrooms
Keywords: навыки перефразирования; исследовательское обучение; эффективное написание резюме текста; paraphrasing skills; inquiry based-learning; effctive summary writing